Analisis Variasi Vertical & Oblique Transmission sebagai Strategi Pewarisan Pengetahuan Paraji di Kecamatan Kadungora, Kabupaten Garut, Jawa Barat - Aleyda Zerlina; Fadly Husain (Yayasan Literasi Sains Indonesia, 2025)
This article aims to analyze the process of paraji knowledge transmission in Cikembulan Village and Rancasalak Village, Garut Regency, West Java. By focusing on how paraji knowledge is transmitted within the family and to someone without paraji bloodline. The purpose of this research does not stop at the process of knowledge transmission, but tries to describe the knowledge of paraji including the pre to post-natal assistance stage as well as understanding the paraji's response to changes and shifts in roles as a result of government policies. The method used is a qualitative method with primary data sources in the form of observation and interview results while secondary data are books, journals, and the internet. The main contribution of this article is to discuss the process of paraji knowledge transmission with a variety of different mechanisms as a local knowledge inheritance strategy. The results show that not only vertical and oblique transmission as a path of inheritance, in the process paraji knowledge can be obtained through unreasonable spiritual experiences. Paraji's knowledge is not considered only as practical knowledge but there are values of patience, spirituality, and local culture in practice making this knowledge necessary to be preserved as part of local wisdom-based knowledge. Although the role of paraji is currently changing, the response of paraji to this change can be said to be positive, as they are collaborative in forming partnerships and realizing the safety of pregnant women and babies.